2012
DOI: 10.1074/jbc.m112.355495
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Damage Induces NF-κB-dependent MicroRNA-21 Up-regulation and Promotes Breast Cancer Cell Invasion

Abstract: Background: DNA damage response and miRNAs have been linked to cancer progression. Results: Genotoxic drug induces up-regulation of miR-21 in a NF-B-and STAT3-dependent manner, which correlates with enhanced breast cancer cell invasion. Conclusion: Genotoxic NF-B activation promotes breast cancer invasion via miR-21 induction. Significance: Genotoxic NF-B signaling pathway may serve as a drug target to reduce therapeutic resistance and metastasis in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(131 citation statements)
references
References 59 publications
12
118
0
1
Order By: Relevance
“…STAT3, a crucial gene in progression of HNSCC, has been previously suggested to up‐regulate miR‐21, in a NF‐κB‐dependent form of IL‐6 up‐regulation 34. Our data from immunofluorescence assay demonstrated that the acidic bile‐induced activated STAT3 and NF‐κB were inhibited by NF‐κB inhibitor in treated HHPC (Figure 6).…”
Section: Resultssupporting
confidence: 59%
“…STAT3, a crucial gene in progression of HNSCC, has been previously suggested to up‐regulate miR‐21, in a NF‐κB‐dependent form of IL‐6 up‐regulation 34. Our data from immunofluorescence assay demonstrated that the acidic bile‐induced activated STAT3 and NF‐κB were inhibited by NF‐κB inhibitor in treated HHPC (Figure 6).…”
Section: Resultssupporting
confidence: 59%
“…Additionally, anti-apoptosis approaches signi cantly improved CVB3-induced heart injury [32,33], further con rming the pathological role of apoptosis in the acute myocarditis. Our results were in line with previous studies that show miR-21 targeting PDCD4 to produce antiapoptotic e ect; however, these studies are mainly focused on the elds of tumor [34][35][36] and vascular diseases [37,38]. Only a few studies report that miR-21 exerts an anti-apoptotic e ect by targeting PDCD4 in heart diseases.…”
Section: Discussionsupporting
confidence: 92%
“…8B). Our previous studies have demonstrated that the transcription of these genes in response to genotoxic stress is regulated by NF-B, which may contribute to reduced apoptosis and prolonged cell survival upon DNA damage (5,16,18). Accordingly, we found that genotoxic drug-induced apoptosis was attenuated in TANK KO cells compared with wild-type cells (Fig.…”
Section: The Tank-mcpip1-usp10 Complex Inhibits Il-1r/tlrmediated Nf-mentioning
confidence: 58%